A importância do agronegócio paranaense - 2005 - Nunes, Paulo Alexandre (2010)
This paper presents the modernization found in agriculture and industry of the state of Paraná, discussing the interaction between these sectors and estimating the input-output matrix for the state of Paraná for the year 2005. Through this array, investigates its productive structure this year, with analysis of rates of binding Rasmussen-Hirschman and pure sectoral multipliers and product, income and employment. The survey thus allows to identify the key sectors for the state economy in 2005. With the result, it was found that agribusiness is a sector of major importance for the Paraná, and is considered key sector, and is one of the main sectors in relation to output multipliers, income and employment. Also through the array of input-output Paraná, it was possible to estimate the participation of agribusiness in the state of Paraná in 2005 in relation to its "PIB". The result was confronted with the findings of Moretto et al. (2002), confirming the trends observed by these authors, such as the decrease of the agribusiness "PIB". There was also a high share of aggregate III compared to the total value of agro-business state in the year 2005.